Reimagining Researchers in Health Research; Comment on "Experience of Health Leadership in Partnering With University-Based Researchers in Canada: A Call to 'Re-Imagine' Research" - Katrina M. Plamondon (Kerman University of Medical Sciences, 2021)
It is widely accepted that research evidence should inform policy and practice in health service organizations. Yet, amid increasingly complex and even wicked realities, where health inequities prevail and resource-strained health service organizations struggle to keep pace with demand, using research to inform practice and policy remains an elusive ideal. Bowen and colleagues' study illuminates critical relational pathways for engagement in evidence-informed practice and decision-making and suggests beginning insights into what might contribute to the tenuousness of this aspirational ideal. But what kind of reimagination is needed to move toward more genuine engagement in research? This commentary argues for reimagining the relationship between researchers and health research, positioning researchers as responsive, guided by humility, and part of a greater collective effort to advance a public good. It challenges notions of objectivity and detached expertise, suggesting that researchers embrace an active practice of humility focused on approaching research in service and from a position of learning rather than knowing.